WAYS TO INCREASE THE VOCABULARY OF SCHOOL-AGED STUDENTS - Ibragimova Muahharam Isakovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: From the point of view of the creative role of activity in social development, of particular importance is its division into reproductive activity (aimed at obtaining an already known result by known means) and productive activities